Research Anthology on Digital Transformation, Organizational Change, and the Impact of Remote Work 2021
DOI: 10.4018/978-1-7998-7297-9.ch098
|View full text |Cite
|
Sign up to set email alerts
|

Future of Education in Industry 4.0

Abstract: With the developments in technology and innovation, the manufacturing, workforce, training, and educational systems were affected. Facing the fourth industrial revolution, academics are researching the possible changes that might arise in education and skills of the future workforce. As the workplace develops, new competencies will surface. With this context in mind, the authors initiated this research. A detailed questionnaire was prepared as a pilot study to comprehend students' views on the use of technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Therefore, vocational guidance at vocational high schools assists students in acquiring valuable skills by establishing specific rules and protocols for doing jobrelated activities with accuracy and efficiency. Scientific presentations promote active participation and increased student attention, supporting the generalization process (Nafea and Toplu, 2021). Study findings indicated that using a demonstration method instead of an explanation approach is more effective for providing vocational training to technical students.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, vocational guidance at vocational high schools assists students in acquiring valuable skills by establishing specific rules and protocols for doing jobrelated activities with accuracy and efficiency. Scientific presentations promote active participation and increased student attention, supporting the generalization process (Nafea and Toplu, 2021). Study findings indicated that using a demonstration method instead of an explanation approach is more effective for providing vocational training to technical students.…”
Section: Discussionmentioning
confidence: 74%
“…These advancements are facilitated by information technologies (Jiang et al, 2024). Companies and the country's education sector must comprehend these changes, along with the associated challenges and opportunities of the new labour market, as failure to do so may lead to a loss of market share (Nafea and Toplu, 2021). The evolving conditions in the labour market are giving rise to novel professions connected to robotics, Big data utilization, the Internet of Things, cybersecurity, cloud computing, augmented reality, and more.…”
Section: Industrial Revolution and Vocational Educationmentioning
confidence: 99%
“…To adapt to the changes and the requirements of the workforce in a digital and intelligent society, the key factors in the success of the new learner generation are classified into two categories: hard skills (analytical skills and research skills) and soft skills (critical thinking, problem-solving, decision-making, creativity, emotional intelligence, communication skills, teamwork skills, negotiation skills, ability to transfer knowledge, and leadership skills) [8]. Progressively, smart educational systems need to focus on creative, innovative, and communicative activities rather than routine activities with monitoring duties, which evolve and consider many promising trends, including opportunities to learn at diverse times and places, personalised learning based on students' capabilities, the use of technological advances and resources, the use of experiential and collaborative learning, student involvement in curriculum design, and increased mentoring approaches [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, it is necessary to design a smart learning environment technically and pedagogically. It should be expanded in space, time, technology, interaction, and control [8] to facilitate and engage learners to experience a seamless learning process and perform tasks in an easy and natural way. Technology covers both hardware and software.…”
Section: Smart Learning Environmentmentioning
confidence: 99%
See 1 more Smart Citation